Combining Imaging Flow Cytometry and Molecular Biological Methods to Reveal Presence of Potentially Toxic Algae at the Ural River in Kazakhstan - Mirasbekov, Yersultan; Abdimanova, Aigerim; Sarkytbayev, Kuanysh; Samarkhanov, Kanat; Abilkas, Aidyn; Potashnikova, Daria; Arbuz, Galina; Issayev, Zhanpeis; Vorobjev, Ivan A.; Malashenkov, Dmitry V.; Barteneva, Natasha S. (Frontiers in Marine Science, 2021)
Algal blooms occur in freshwater bodies throughout the world, often leading to fish kills. Cases of these kills along the Ural River were reported in 2018–2019, involving significant amount of sturgeon in fish farming areas. In this study, the analysis of algal samples from the Ural River's delta up to 100 km inland was carried out from August–December 2019 using imaging flow cytometry (IFC), molecular biological, and microscopic techniques. We identified the filamentous cyanobacteria Cuspidothrix issatschenkoi, Dolichospermum cf. flos-aquae, Dolichospermum cf. macrosporum, Pseudanabaena limnetica and Planktothrix spp. as the dominant potentially toxic phytoplankton species, and we also found minor quantities of Cylindrospermopsis raciborskii. For the first time, molecular phylogenetic investigations of field clones of cyanobacteria from Ural River were carried out to establish the taxa of the dominant species, and to identify the presence of genes encoding toxins. The complementary analysis with nanopore-based next generation sequencing overlapped with the results of IFC and was instrumental in revealing minor cyanobacterial taxa. Real-time PCR analysis and Sanger sequencing indicated the presence of Microcystis and ADA-clade spp. as well as genes associated with the production of microcystin (mcyE) and the algal neurotoxin saxitoxin (sxtA) originating from cyanobacteria. These findings suggest that toxin-producing cyanobacteria could become a threat in the Ural River near Atyrau, which can significantly affect aquaculture in the region.